Prevalence of aetiological pathogens of vaginal discharge and male urethritis syndromes in the Tshwane region - Kock, Marleen Magdalena (University of Pretoria, 2016)
Dissertation (MSc (Medical Microbiology))--University of Pretoria, 2015.